2001
DOI: 10.1046/j.1468-1331.2001.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Twelve‐month safety of entacapone in patients with Parkinson’s disease

Abstract: The safety of entacapone combined with levodopa and a dopadecarboxylase (DDC) inhibitor was tested in a 12-month double-blind study of 326 patients with idiopathic Parkinson's disease (PD). The study population represented 'typical' PD outpatients, including patients with varying disease severity and with various concomitant medications. Two-thirds of the patients were randomized to receive 200 mg of entacapone with each of 2--10 daily levodopa doses, and one-third to receive placebo. All entacapone patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
0
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 21 publications
7
46
0
3
Order By: Relevance
“…These studies have shown that completing levodopa therapy with adjunct entacapone consistently increases daily ‘on’ time (and correspondingly decreases ‘off’ time), and results in significantly increased motor function while ‘on’ [13,14,15,16,17]. This current investigation is the first to compare the efficacy of switching to Stalevo versus initiation of separate entacapone with traditional levodopa/DDCI in those patients experiencing end-of-dose wearing-off.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These studies have shown that completing levodopa therapy with adjunct entacapone consistently increases daily ‘on’ time (and correspondingly decreases ‘off’ time), and results in significantly increased motor function while ‘on’ [13,14,15,16,17]. This current investigation is the first to compare the efficacy of switching to Stalevo versus initiation of separate entacapone with traditional levodopa/DDCI in those patients experiencing end-of-dose wearing-off.…”
Section: Discussionmentioning
confidence: 93%
“…The efficacy, safety and tolerability of entacapone (in combination with traditional levodopa/DDCI) has been proven in several phase III clinical trials [13,14,15,16,17,18]. These trials have shown that entacapone extends the ‘on’ time up to 1.7 h a day, reduces ‘off’ time (by 1.1–1.6 h a day) and significantly improves motor function and activities of daily living [13,14,15,16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…These may be managed by reducing the dose of levodopa [4, 6, 11]. The larger number of dopaminergic AEs seen with levodopa/DDCI and entacapone is probably due to the increased levels of plasma levodopa.…”
Section: Discussionmentioning
confidence: 99%
“…One study had a randomized double blind cross-over design [43], the remaining seven studies had a randomized, double-blind parallel-group design [44][45][46][47][48][49][50]. One was a phase II study [43], the remaining seven were phase III studies.…”
Section: Comt Inhibitors Entacaponementioning
confidence: 99%